Cultural Responsiveness and Mental Health Engagement Among Latino Adolescents: A Scoping Review - Dushawn A. Powell (Research on Social Work Practice, 2026)
Purpose This scoping review mapped school-based programs and interventions designed to increase engagement in mental healthcare among Latino adolescents in the United States. Method Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidance, a search of five databases plus reference-list hand-searching identified 259 records; eight studies met inclusion criteria. Data were synthesized through descriptive mapping and thematic analysis. Results Six themes emerged, including cultural responsiveness, family engagement, school-based delivery, and peer support. Only one intervention was culturally adapted for Latino youth. No study used a validated engagement measure, engagement indicators were not comparable, only one study reported confidence intervals, and the single trial testing a family-centered adapted intervention against usual care found no between-group difference. Discussion Cultural responsiveness is best understood as a plausible but untested mechanism rather than a demonstrated one. School social workers should document participation and retention by language and ethnicity.